2018
DOI: 10.1002/etc.4216
|View full text |Cite
|
Sign up to set email alerts
|

Riparian spiders indicate the magnitude and sources of polychlorinated biphenyl contamination at a large contaminated sediment site

Abstract: We investigated polychlorinated biphenyl (PCB) contamination at the Ashtabula River (northeast OH, USA) area of concern following remedial dredging using araneid and tetragnathid spiders. The PCB concentrations remain elevated in the area of concern compared with reference conditions. Patterns of contamination were strikingly similar between taxa, but were higher in tetragnathids at the most contaminated sites. Spider PCB homolog distributions identified 2 PCB sources to the area of concern. Based on these fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The ecological interactions of spiders, the most abundant terrestrial arthropod predator group found on every life‐supporting landmass, are pivotal in many ecological networks (Riechert & Lockley, ; Turnbull, ). As such, they have received a lot of attention by food web ecologists of diverse fields including pest control (Holland et al, ), pollutant transfers (Kraus et al, ; Walters, Otter, Kraus, & Mills, ), and cross‐ecosystem fluxes (Lafage et al, ). Spiders feed on predigested fluids of their prey, restricting field studies of spider diet to direct observation, stable isotope analysis, and molecular analysis (Birkhofer et al, ; Pompanon et al, ; Symondson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ecological interactions of spiders, the most abundant terrestrial arthropod predator group found on every life‐supporting landmass, are pivotal in many ecological networks (Riechert & Lockley, ; Turnbull, ). As such, they have received a lot of attention by food web ecologists of diverse fields including pest control (Holland et al, ), pollutant transfers (Kraus et al, ; Walters, Otter, Kraus, & Mills, ), and cross‐ecosystem fluxes (Lafage et al, ). Spiders feed on predigested fluids of their prey, restricting field studies of spider diet to direct observation, stable isotope analysis, and molecular analysis (Birkhofer et al, ; Pompanon et al, ; Symondson, ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings underscore the importance of considering taxon when designing and evaluating screening‐level ecological risk assessments because the taxa sampled can have substantial effects on the conclusions reached. For sites contaminated with MeHg, we suggest that tetragnathid tissue concentrations are preferable to other taxa because they not only provide a conservative estimate of risk but also may provide an additional line of evidence that, if necessary, could be used to characterize the effectiveness of future remediation efforts (e.g., Kraus et al 2017; Walters et al 2018). We do note that the utility of tetragnathids is contingent on their abundance, and their use may be complicated by biomass requirements necessary to achieve target method detection limits (Beaubien et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To date, no study has examined the importance of different spider taxa in the calculation of MeHg risk to birds. Given the recent results of Ortega‐Rodriguez et al (2019) and Walters et al (2018), which demonstrated that both MeHg and PCB concentrations can vary significantly among riparian spider taxa, it is important to determine whether taxa differences are great enough to warrant consideration in risk assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Increased erodibility results in a decrease in the depth of fertile topsoil and an increase of sediment within streams. These sediments often contain metals such as lead, chromium or zinc, pesticides such as DDT, other organics such as polychlorinated biphenyls (PCBs) or polycyclic aromatic hydrocarbons (PAHs), or various other synthetic chemicals that may be toxic to aquatic and terrestrial species, and may also be linked to human health via the food chain (see, for example: Pavlović et al, 2016;Walters et al, 2018;Bing et al, 2019).…”
Section: Effects Of Urbanizationmentioning
confidence: 99%